Microstructural features of Sc- and Zr-modified Al-Mg alloys processed by selective laser melting. (5th February 2017) - Spierings, A.B.; Dawson, K.; Heeling, T.; Uggowitzer, P.J.; Schäublin, R.; Palm, F.; Wegener, K.
Abstract: Selective Laser Melting (SLM) is an additive manufacturing technology that offers significant potential for lightweight applications in space, aerospace, and automotive industries as well as in mechanical engineering. Structural aluminium alloys are therefore of special interest. Scalmalloy® is a scandium-modified Al-Mg alloy which displays exceptional properties when processed by SLM. These properties are predominately related to a generally very fine grained microstructure. However, the fine grained microstructure interspersed with coarser grained regions. Microstructural analyses indicate that the temperature regime and the particle precipitation behaviour are responsible for the duplex grain structures. In melt pool areas close to the pool base, numerous Al3 (Sc, Zr), Al-Mg-oxides and mixed particles act as nuclei for Al matrix solidification, leading to the formation of a very fine grained microstructure. In hot melt pool areas with T > 800 °C the majority of particles dissolve and growth of coarse columnar grains takes place. Better understanding of the formation mechanisms for these two distinct different structures will help pave the way towards newly designed alloy compositions for the SLM process. Graphical abstract: Highlights: Comprehensive description of the microstructure. Additive manufactured Scandium and Zirconium modified AlMg alloys exhibit a bi-modal grain size distribution. The formation fine-grained microstructure is closely related to the presence of intermetallic particles in the melt pool. Precipitate survival is affected by local temperature distribution in the melt-pool.